THE EFFECT OF SMOKING HABITS ON THE OCCURRENCE OF BRUXISM: A RAPID REVIEW: PENGARUH KEBIASAAN MEROKOK TERHADAP TERJADINYA BRUXISM : A RAPID REVIEW - Prida Lani Debora P; Rasmi Rikmasari; Seto Pramudita (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Bruxism is a parafunctional habit in the oral cavity area. Bruxism is distinguished from awake and sleep bruxism. Bruxism is caused by various etiological factors. Smoking habits are considered is one of the exogenous factors that cause bruxism. This study aims to determine the effect of smoking habits on bruxism. Review: This study was conducted using the rapid review of articles reporting the effect of smoking on the occurrence of bruxism. Article searches were conducted through PubMed, Google Scholar, and EBSCO Host from October until November 2022. Article screening was carried out by checking for duplication, reading titles and abstracts, and reading the contents of the entire text. A total of 1257 articles were identified at the initial stage of the research with total of 6 articles included into rapid review criteria. Research on articles analyzed qualitatively shows that smoking habits affect occurrence of bruxism in most of the articles reviewed. As many as 2 articles prove smoking influences bruxism in general and as many as 2 articles proving that smoking affects awake bruxism. Conclusion: Smoking habits have an influence on the occurrence of bruxism in general.